Students’ Perspectives on Mental Health: Using World Cafés to Engage in Dialogue about Health Promotion and Support Services - de Moissac, Danielle; Waddell. M, Candice M.; Smith, Nadine; Rocque, Rhéa (Collected Essays on Learning and Teaching, 2020)
With the increased incidence of poor mental health in young adults, health promotion strategies are needed on campuses. World Cafés were held to facilitate discussion around three main topics: thoughts about findings emerging from a recent health survey, resources currently available on campus, and strategies or resources needed to improve student well-being. Participants readily provided insight into mental health concerns among students, and their recommendations focused primarily on creating a culture of well-being in the university with more professional support services and greater health promotion. Overall, the World Café approach provided an effective method to engage students and discuss possible strategies to promote better mental health on campus. Étant donné l’augmentation des problèmes de santé mentale chez les jeunes adultes, il faut adopter des stratégies de promotion de la santé à l’université. Des conversations de type Café du monde – World Café – ont eu lieu autour de trois sujets : 1) des réflexions autour des résultats provenant d’un sondage récent pourtant sur la santé; 2) les ressources qui sont actuellement offertes à l’université; 3) les stratégies et les ressources nécessaires à l’amélioration du bien-être des étudiants. Les participants n’ont pas hésité à témoigner des enjeux de santé mentale dans la communauté étudiante. Leurs recommandations ont convergé principalement vers la création d’une culture du bien-être à l’université, ce qui suppose un accroissement des services d’aide professionnelle et de la promotion de la santé. Dans l’ensemble, la méthode de type Café du monde a permis de faire participer les étudiants et de discuter des stratégies potentielles pour la promotion de la santé mentale à l’université.

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.